Teaching collocations through web-based concordancing: A corpus informed quasi-experimental study - Kızıl, Aysel Şahin; Kilimci, Abdurrahman (My University, 2017)
With the advent of language corpora and concordancing activities, teaching collocations knowledge of which is considered significant for appropriate and fluent language use has gained new dimensions within the context of technology enhanced language learning. The present study investigates the impact of web-based concordancing activities on EFL learners’ achievement and retention of verb-noun collocations compared to paper based-activities. A total of 62 EFL learners participated in the study by taking a pre-test and an immediate and a delayed post-test. Results indicated that learners in experimental group outperformed the control group making significant improvement in their knowledge of verb-noun collocation immediately after the web-based practice. Although both groups regressed later, final performance of the experimental group was still better than that of control group. This study, therefore, suggests that EFL practitioners craving for creating variations in their instructional settings employ web-based concordancing activities to raise collocational competence of learners.
Kitap - Kitap İçinde Yayın (Bölüm ya da Makale)
Keywords: EFL; Corpus informed intervention; Data driven learning; Concordancing; Collocation